2017
DOI: 10.1108/bfj-07-2016-0314
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual understanding of criminality and integrity challenges in food supply chains

Abstract: Purpose Business, consumers and governmental organisations are harbouring a growing need to gain an appreciation of behaviours connected to food criminality. In order to acquire a cross-functional understanding of these thematic areas (crime and fraud) the mapping of existing research is needed. The paper aims to discuss these issues. Design/methodology/approach This paper contributes to the process of knowledge understanding, by systematically reviewing literature to provide an analysis of the current body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Whist many of these technologies and systems will be focused upon the large food manufacturing companies and secondary production providers (such as packaging, logistics, and warehousing), more elementary yet critical technologies and systems are required by the small food suppliers. The respondents from the small food companies that were surveyed identified that developing a sound knowledge of digital marketing and e-Word of Mouth (e-WoM) [29][30][31][32] is in great demand in order to ensure that smaller companies achieve greater visibility with a wider range of customers and more immediate feedback from clients in order to remain at the forefront of the product development process [59]. Allied to this issue is the enhancement of a company's use of Social Media systems to include correct website development with enhanced capabilities for order-making, payments, and special product requests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whist many of these technologies and systems will be focused upon the large food manufacturing companies and secondary production providers (such as packaging, logistics, and warehousing), more elementary yet critical technologies and systems are required by the small food suppliers. The respondents from the small food companies that were surveyed identified that developing a sound knowledge of digital marketing and e-Word of Mouth (e-WoM) [29][30][31][32] is in great demand in order to ensure that smaller companies achieve greater visibility with a wider range of customers and more immediate feedback from clients in order to remain at the forefront of the product development process [59]. Allied to this issue is the enhancement of a company's use of Social Media systems to include correct website development with enhanced capabilities for order-making, payments, and special product requests.…”
Section: Discussionmentioning
confidence: 99%
“…The following section details the drivers, inputs, and outputs of the framework. Core supply chain capabilities: virtual enterprises, digital marketing, and virtual supply chain environments focusing upon Information Communication Technologies (ICT) and web technologies by partnering/outsourcing companies [59]. Increase the transparency of operations through to the supply chain in order to achieve greater food security and reliability [60].…”
Section: Towards the Implementation Of Smart Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Food fraud and adulteration is defined as a dishonest act or omission related to the sale or preparation of food which is intended to generate personal economic benefit or damage to a third party (12). The types of food adulteration described in animal products are defined in Table I.…”
Section: Understanding Food Fraud and Adulterationmentioning
confidence: 99%
“…Conversely, if the factors that influence food integrity are similar to those that affect the concerns about applications of these technologies, then the measures that improve food integrity standards and consumer confidence in these standards can also influence the acceptance of these technologies. Researchers have looked at many aspects of food integrity: food safety and quality assurance [2,[19][20][21][22][23], supply chain management [16,[24][25][26], and so forth. Other studies have examined the issue of food integrity in the context of specialized foods (see [18]).…”
Section: Literature Reviewmentioning
confidence: 99%